The relationship between knowledge and personal hygiene and the occurrence of sexually transmitted diseases at the Community Health Center Talise, Palu - Andi Mariani; Arifin Seweng; Syamsiar S. Ruseng; Apik Indarty Moedjiono; Tahir Abdullah; Alam Anshary; Rosmala Nur; Muhammad Basir; Mahfudz; Sabir (Elsevier, 2021)
Objective: This morbidity rate has increased compared to the results of a survey in 2012, which were 16,110 cases of STDs, and 11,141 cases in 2010. This study aimed at determining the relationship between knowledge and personal hygiene and the incidence of sexually transmitted diseases in adolescents at the Community Health Center Talise, Palu. Methods: This study utilized a case-control study design to assess the relationship between knowledge and personal hygiene and the occurrence of sexually transmitted diseases. There were 84 samples in this study involving 42 cases and 42 controls. Data collection was carried out using a questionnaire. Result: The variable of personal hygiene showed that the Chi-Square test results provided a value of p = 0.016, which means that the difference between individual hygiene and the incidence of sexually transmitted diseases (STDs) in adolescents was significant (p < 0.05). Conclusion: This study concludes that the OR calculation has a value of 4.6, which means that adolescents who have insufficient knowledge have 4.6 times greater risk of suffering from STDs than adolescents who had sufficient knowledge.